Cytoskeletal Transport, Reorganization, and Fusion Regulation in Mast Cell-Stimulus Secretion Coupling - Ménasché, Gaël; Longé, Cyril; Bratti, Manuela; Blank, Ulrich (Frontiers in Cell and Developmental Biology, 2021)
Mast cells are well known for their role in allergies and many chronic inflammatory diseases. They release upon stimulation, e.g. via the IgE receptor, numerous bioactive compounds from cytoplasmic secretory granules. The regulation of granule secretion and its interaction with the cytoskeleton and transport mechanisms has only recently begun to be understood. These studies have provided new insight into the interaction between the secretory machinery and cytoskeletal elements in the regulation of the degranulation process. They suggest a tight coupling of these two systems implying a series of specific signaling effectors and adaptor molecules. Here we review recent knowledge describing the signaling events regulating cytoskeletal reorganization and secretory granule transport machinery in conjunction with the membrane fusion machinery that occur during mast cell degranulation. The new insight into MC biology offers novel strategies to treat human allergic and inflammatory diseases targeting the late steps that affect harmful release from granular stores leaving regulatory cytokine secretion intact.